Air Pollution from the Burning of Fuels Derived from Petroleum in Motor Vehicles - Drumm, Fernanda Caroline; Gerhardt, Ademir Eloi; Fernandes, Gabriel D'Avila; Chagas, Patricia; Sucolotti, Mariana Scheffer; Kemerich, Pedro Daniel da Cunha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The pollution generated in large urban centers follows mainly from burning fossil fuels, basically gasoline and diesel, which are mineral substances formed by carbon compounds from the decomposition of organic materials, what take millions of years. Therefore, they are considered non-renewable resources. The fuel burning occurs incompletely when employed in heat engines and automotive vehicles, and this process results in release of a large amount of carbon monoxide and carbon dioxide emissions, making these great villains regarding to global warming and the greenhouse effect. It is worth noting that these fuels feed the industrial, electrical and transport of most world economies. This work aims to raise issues related to air pollution from motor vehicles use.